VOWEL HARMONY IN D&D (MO) - ADJEI-MENSAH, MRS. SUSANA (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This paper explores the existence of vowel harmony in a language spoken in parts of Brong Ahafo and Northern Regions of Ghana in West Africa. This qualitative research was conducted with the help of native speakers of the language. It was harmony as well as Cross-height vowel harmony exist in the language